Hubungan Dukungan Suami dengan Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan Di RSI Siti Khadijah Palembang - Putri, Sartika Dwi Yolanda; Putri, Harlinda Widia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anxiety is a feeling experienced by pregnant women that is uncertain due to feelings of restlessness, unease due to a threat during pregnancy. The aim of this research was to determine the relationship between therapeutic communication, husband's support and parity with third trimester pregnant women's anxiety in facing childbirth at the Siti Khadijah Islamic Hospital in Palembang in 2019. The research design used was an analytical survey method with a cross sectional approach. The population of this study were all third trimester pregnant women who visited the Siti Khadijah Islamic Hospital in Palembang at the time the research was conducted, totaling 126 people, with a total sample of 56 respondents taken using simple random sampling technique. The results of this study show that there is a relationship between therapeutic communication and anxiety in pregnant women (ρ value=0.013). husband's support and pregnant women's anxiety (ρ value=0.023). parity with anxiety of pregnant women at Siti Khadijah Islamic Hospital Palembang in 2019 (ρ value=0.030). It is recommended that health workers, especially midwives, inform husbands or families, especially pregnant women, about the importance of family support, especially husbands, for their pregnant wives. Providing information can be done by distributing leaflets and counseling about the role of husband's support for his pregnant wife.